Zakat untuk Perekonomian Umat (Studi Kasus di Kecamatan Sihapas Barumun Padang Lawas, Sumatera Utara) - Pendi Hasibuan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
In conclusion, zakat, a fundamental aspect of Islam, can significantly improve the local economy when professionally administered. Effective zakat management positively affects mustahiq, the eligible recipients, thus making the intended purpose of zakat successful. Adopting a productive zakat approach, emphasizing productivity, proves promising in combating poverty and enhancing economic conditions. This qualitative research investigates productive zakat management in Sihapas Barumun sub-district, Padang Lawas, North Sumatra, using interviews. The findings illustrate the successful economic empowerment of mustahiq and their upliftment from poverty. Zakat managers diligently identified eligible recipients and provided financial assistance or livestock. This study emphasizes the positive impact of well-managed zakat and advocates its responsible allocation to promote socioeconomic progress within communities.